Analisis Gaya Bahasa dalam Slogan Iklan Mie Sedap - Rabiyatul Adawiyah; Bukhori Muslim (Universitas Nahdlatul Wathan Mataram, 2023)
This research aims to describe the types of figurative language and the meaning of figurative language contained in the Mie Sedap Advertising Slogan. The data source for this research is the 2019-2023 Mie Sedap advertisement. Data was obtained using listening and taking notes. Data containing figurative language are then analyzed descriptively qualitatively based on the theory of figurative language proposed by Tarigan (1985) and Leech (1974) regarding meaning. The research results show that there are 16 figurative languages contained in the Mie Sedap Advertisement, namely 2 data for repetition, 4 data for personification, 5 data for hyperbole, 2 data for alliteration, 1 data for metaphor, 1 for simile and also 1 for synecdoche. Hyperbole and personification are the dominant types of figurative language found in Mie Sedap Advertisements. Meanwhile, the meaning of figurative language tends to use a combination of connotative, denotative, stylistic and affective meanings.